Penerapan VPN Dalam Topologi Star Untuk Keamanan Pengiriman Data - Tiara Pramesti Wulandari; Novaldi Ramdani Reza; Errisa Zulqa Deswana; Muhammad Rifqi Adillah; Didik Aribowo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Building a computer network needs significant care in selecting a configuration to ensure its efficacy and efficiency. It involves decisions about network topology, types, and device use. Security measures are essential for protecting networks with internet access from external attacks. A study conducted at an Islamic university in Indonesia indicated the use of a star network architecture and a client-server network model. The servers utilize Debian Linux. The university's security infrastructure includes a server authentication system and the setting up of a Virtual Private Network (VPN). If the server authentication difficulty is caused by a power outage, it is recommended that you use an UPS (uninterruptible power supply) to preserve power stability. Overall, security methods show up to be more effective when firewalls are installed.